Being And Nothingness In The Poetry Of Abi Ala Al Maari (death and a sense of mortality as a model) (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
There is no doubt that life and death formed a large part of human existence, and anxiety and confusion occupied his mind as he kept pace with this vital continuity between life and its requirements on the one hand, and the power and power of death on the other hand, and death is the opposite of life because of its strangeness that raises wonder in the human soul and the secret of life remains in the hearts humans have a direct impact on souls, as al maari was preoccupied with human destiny, what awaits a person after death? This issue took human undeniable effort from him, as ittook him to broad horizon in which religious faith mixes with philosophical thought, and this sad view turns into a new vision that goes beyond the appearance of life that the senses perceive to its secret lurking in its depths, then his sorrows turn into philosophical reflections that take in a large part the form of judgment, and from which he ended up with opinions on life and death through his experience that he lived, and also his deep philosophical culture.